2019
DOI: 10.1016/j.artd.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement failure due to adverse local tissue reaction from both ceramic abrasive wear and trunnion corrosion

Abstract: The most common sources for metal ions after total hip arthroplasty (THA) are the bearing surface in metal-on-metal articulations and trunnion corrosion. Concomitant dual interface failure is an uncommon complication in metal-on-polyethylene THA. We report an unusual case of a 59-year-old woman with ceramic-on-ceramic THA in 2005, who underwent revision to metal-on-polyethylene THA 4 years later after femoral head fracture. Subsequently, she developed substantial adverse local tissue reaction and significant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…5a). Metallosis after total hip arthroplasty is a subject that has attracted high research in recent years after the reported association with potential adverse outcomes [2]. As of March 2019, there are no FDA-approved metal-on-metal total hip replacement devices currently on the market in the USA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…5a). Metallosis after total hip arthroplasty is a subject that has attracted high research in recent years after the reported association with potential adverse outcomes [2]. As of March 2019, there are no FDA-approved metal-on-metal total hip replacement devices currently on the market in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical mistakes, inexperience, and procedural challenges have been implicated in metallosis [3]. Revision surgeries replacing a failed plastic or ceramic implant with metal-on-metal total hip arthroplasty have posed a high chance of 3rd body wear [2]. A truncated acetabular component has also been linked to metallosis, owing to accelerated mechanical wear from 3rd body, which usually occur at an articulation between intentional bearing surfaces in the presence of wear debris.…”
Section: Surgical Procedural Mistakes and Errorsmentioning
confidence: 99%
See 3 more Smart Citations